Meromorphic dynamics - Kotus, Janina; Urbański, Mariusz (Cambridge : Cambridge University Press, 2023)
"The second of two volumes builds on the foundational material on ergodic theory and geometric measure theory provided in Volume I, and applies all the techniques discussed to describe the beautiful and rich dynamics of elliptic functions. The text begins with an introduction to topological dynamics of transcendental meromorphic functions, before progressing to elliptic functions, discussing at length their classical properties, measurable dynamics and fractal geometry. The authors then look in depth at compactly non-recurrent elliptic functions. Much of this material is appearing for the first time in book or paper form. Both senior and junior researchers working in ergodic theory and dynamical systems will appreciate what is sure to be an indispensable reference"--
Volume 1. abstract ergodic theory, geometry, graph directed Markov systems, and conformal measures -- Volume 2. Elliptic functions with an introduction to the dynamics of meromorphic functions.
Includes bibliographical references and index.
Keywords: Functions, Meromorphic; Topological Dynamics of Meromorphic Functions; Elliptic Functions: Classics, Geometry, and Dynamics; Compactly Nonrecurrent Elliptic Functions